S119 Variation in pharyngeal pH in the diagnosis of airway reflux. (16th November 2010) - Molyneux, I D; Jackson, W; Morice, A H
Abstract : Introduction and objectives: Reflux of gastric contents to the laryngopharynx has been implicated in the pathogenesis of chronic cough and may exacerbate other respiratory conditions. Direct measurement of pharyngeal pH is available but standard analysis relies on the pH crossing a lower threshold. Non-acid gaseous reflux may cause respiratory symptoms without producing a significant drop in pharyngeal pH. We theorised that variation in pharyngeal pH might be a useful marker of airway reflux. Methods: Measurements of pH in the pharynx over 24 h were made in patients with a variety of respiratory diagnoses suspected to have reflux contributing to their symptoms. Diagnoses included chronic cough, cystic fibrosis and asthma. Results were analysed using a pre-defined, threshold-based scoring system and our novel system based on variation in pH. Comparison was also made with oesophageal physiology where available. Results: 60 studies were performed on 58 patients; median age 48 years (range 17–81). 43 studies had an abnormal threshold score. 31 patients had an abnormal variation score (>30 events per hour). Both were positive in 21 patients and both negative in 7. Cough symptom scores were similarly high in patients with abnormal variation to those with abnormal threshold scores (mean 34.7 and 38.3 respectively) and higher than patients with both negative (23.0; n/s). Cough patients who had undergone fundoplication demonstrated less variation than those who had not (mean events 55 per hour vs 115; n/s). Asthma patients had similar overall variation to other groups but had higher numbers of events over fewer peak hours (468 vs 368 events per peak hour; p=0.08) with the opposite seen in cystic fibrosis patients (276; p=0.26). Of 25 patients with an abnormal pharyngeal study and an oesophageal study available, 15 had normal oesophageal studies. Conclusions: These results show that the interaction between pharyngeal pH and airway symptoms is complex, not easily assessed using a pH threshold alone and not well correlated with oesophageal physiology. Assessment of variation suggests different patterns of reflux may relate to disease phenotypes. The ideal analysis should include correlation of clinical symptoms with peaks in variation and pH threshold events.